(untitled) (Circe de clásicos y modernos, 2019)
The main question of analysis in this study is the education conceived by Licurgo as a task of the State. Practiced in Crete, in which Lycurgus had been educated, it was taken to Sparta, from where it spread to all Greek civilization. The proposal of Lycurgus, under different practices and interpretations, inspired not only the legislatures, but also the subsequent philosophical discussion. The Republic of Plato, here conceived as a project of legislature (politeía) and of philosophical education, is evaluated in terms of a mature synthesis of the educational task of the State.